Median Canaliform Dystrophy of Heller occurring on thumb and great toe nails - Pathania, Vikas (Med J Armed Forces India, 2016)
Median Canaliform Dystrophy of Heller is a rare but morphologically striking habit tic deformity of thumb nails characterized by midline longitudinal furrow with multiple transverse parallel lines. The proposed etiopathogenesis is repetitive trauma to the nail plate and cuticle, however some case reports have suggested familial occurrence and use of oral retinoids in its causation. Treatment is often prolonged and unsatisfactory, though some topical agents have been used successfully. We report a case of a young male patient presenting with Median Dystrophy of Heller affecting both Great thumb and toe nails simultaneously.